Perbaikan Layanan Puskesmas Bahu Kecamatan Malalayang Dengan Metode SERVQUAL dan Zone of Tolerance - Ronaldo F.I Rottie; Tryadi W. Tumewu (Universitas Katolik Musi Charitas, 2020)
Indonesia is the largest archipelago country in the world with hundreds of islands stretching from Sabang to Merauke. Health service centers in all corners of the region are starting to develop and so many people need health services. Puskesmas is an organization under the Ministry of Health of the Republic of Indonesia which functions to provide public health services to people at the sub-district or regional level. The Shoulder Puskesmas, Malalayang District, is one of the integrated service centers, acceptable and accessible to the community in Malalayang District. The results of observations and interviews in the field showed that there were some services that were lacking so that there were complaints from residents who came for treatment. Complaints include lack of parking space, lack of medicines, poor cleanliness of the Puskesmas, lack of queuing seats, less clean toilets, and a lack of service information. Based on these initial indications, it is necessary to improve the quality of services at the Shoulder Health Center. SERVQUAL and ZOT are used to measure the level of satisfaction of Puskesmas services and identify criteria under tolerance limits. This study used 150 respondents. The validity and reliability tests were conducted using 30 respondents to get the results that the questionnaire is valid and reliable. The results of data processing show that attributes 1, 3, 9, 13, 15, and 16 are minus ZOT width values, thus these attributes are a priority for improving the quality of Puskesmas services.